Improving occupational safety and health of slickline operations based on proton's experience - Mohd. Zairen Mohammad Zin, 1990-, author 613706; Issham Ismail 1960- supervisor 632742; Fakulti Kejuruteraan Kimia dan Kejuruteraan Tenaga 599090 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Kejuruteraan (Petroleum)) - Universiti Teknologi Malaysia, 2017